Risk Factors for Severe Pneumonia According to WHO 2005 Criteria Definition Among Children <5 Years of Age in Thai Binh, Vietnam: A Case-Control Study - Van Thuan Hoang; Thi Loi Dao; Philippe Minodier; Duy Cuong Nguyen; Nang Trong Hoang; Van Nghiem Dang; Philippe Gautret (Springer, 2019)
Vietnam is one of the 15 countries where the prevalence of child pneumonia is highest. It is a major cause of admission in pediatric hospitals. However, little is known on the burden of severe pneumonia and their risk factors in children <5 years of age in Vietnam. A case-control study was conducted among children aged 2-59 months presenting with pneumonia at the Pediatric Provincial Hospital of Thai Binh. Cases were children with severe pneumonia while controls included those with non-severe pneumonia as defined by the World Health Organization (WHO) classification of 2005. Eighty-three cases and 83 controls were included. Sex ratio was 2.19. Children with severe pneumonia were significantly less likely to receive antibiotics preadmission compared to children with non-severe pneumonia [odds ratio (OR) = 0.16, 95% confidence interval (CI) = 0.06-0.42]. The main risk factors of severe pneumonia were a lack of immunization (OR = 4.77, 95% CI = 1.80-12.65), an exposure to cigarette smoke (OR = 3.87, 95% CI = 1.62-9.23), and having a mother with a low level of education. Children with severe pneumonia were 25 times more likely to present with associated measles with p < 0.0001 and five times more likely to present with diarrhea than children with non-severe pneumonia (p < 0.0001). Improving immunization coverage, educating parents about the risks of passive smoking and the recognition of respiratory distress signs, and facilitating early antibiotic access for infants with acute pulmonary disease should reduce the burden of such illnesses. To implement a national, multicenter study about pneumonia in children, more precise inclusion criteria should be chosen, including radiological and/or biological assessment.